Large scale and facile sonochemical synthesis of magnetic graphene oxide nanocomposites and their dual electro/magneto-stimuli responses. Issue 81 (16th August 2016) - Zhang, Wen Ling; Tian, Yu; Liu, Ying Dan; Song, Zhong Qian; Liu, Jing Quan; Choi, Hyoung Jin
Abstract : Magnetic Fe3 O4 /GO nanocomposites have been prepared via an effective electrostatic strategy under ultrasonic waves. Their appealing dual electro/magnetorheological (ER/MR) performances were investigated under applied electric or magnetic fields. Abstract : Graphene based magnetic nanoparticles (NPs) have attracted considerable attention in numerous applications owing to their splendid chemical and physical properties. However, the synthesis approaches are often complex and relatively expensive. In the present study, we report the fabrication of magnetic graphene oxide (GO) nanocomposites (denoted as Fe3 O4 /GO) via an effective electrostatic strategy under ultrasonic waves using the bare Fe3 O4 NPs initially synthesized via a co-precipitation method. The Fe3 O4 NPs were uniformly covered by the crumpled-like GO matrix, as confirmed by transmission electron microscopy. Their structure and magnetic behaviors were investigated via Fourier transform infrared spectroscopy and vibrating sample magnetometer curves. The appealing dual electro/magnetorheological performance of the as-prepared Fe3 O4 /GO dispersed in silicone oil was investigated using a rotational rheometer under applied electric or magnetic fields, respectively. Their dynamic yield stress values were analyzed using a universal equation, and the MR efficiency was observed to be higher than that of the ER.